The Role of Technology in Mental Health: Evaluating Digital Interventions for Psychological Well-being (International Journal of Scientific Research in Science and Technology, 2024)
Digital health interventions (DHIs) have emerged as a promising approach to address mental health issues across various demographics, including different age groups, cultural contexts, and socio-economic backgrounds. This review aims to critically examine the role of digital interventions in mental health, focusing on their effectiveness, benefits, and limitations compared to traditional therapies. The review seeks to assess various digital tools, including mobile apps, online therapy platforms, AI-driven solutions, virtual reality (VR) therapies, and wearable technologies, to determine their impact on mental health outcomes. In addition, the review explores the challenges of implementing these technologies, such as data privacy concerns, the digital divide, and regulatory issues, while highlighting opportunities for innovation and integration into traditional healthcare systems. Policymakers are faced with the daunting challenges of managing rapid innovation against concerns with respect to data privacy and security and ethical considerations related to applications of AI and IoT.